TEKNIK BUZZ GROUP DAN TEKNIK GROUP EXERCISES SEBAGAI STRATEGI MENINGKATKAN SELF-EFFICACY PENGAMBILAN KEPUTUSAN KARIR - muhamad ayub (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
The purpose of this study was to test the effectiveness of the buzz group technique and group exercises technique to increase self-efficacy in making career decisions for students of MAN 1 Kota Serang. The experimental design method used in this study was the